IMPLEMENTASI TEKNIK KLARIFIKASI NILAI TERHADAP AKTIVITAS BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PKN - Kusnadi; Elvita, Jumia (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This article aims to discuss the implementation of value clarification techniques for student learning activities in Civics learning in SMK. The observation of case studies from various assessments of all student characteristics reviewed and on learning only focuses on cognitive aspects and little attention is paid to the emotional aspects of participants. This has implications for the lack of student activity in subjects, which ultimately refers to the achievement of learning objectives, the culture of learning activities, and personality values that will affect student learning outcomes. For this reason, researchers try to make changes in learning models with an approach through value clarification techniques. This class action research is carried out with two cycles, the research subjects of which are class XI students. For cycle 1 results, out of 30 students, only 24 (80%) students completed the formative (oral) test. Furthermore, in cycle 2, 27 (90%) students completed it, with an overall average score of 75.66. From the results of the analysis that researchers have carried out, it can be concluded that the implementation of Value Clarification Techniques for student education activities in the field of citizenship has run significantly at SMK Migas Teknologi Riau for the 2022/2023 academic year.